2005
DOI: 10.1111/j.1365-3024.2005.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigens from Ascaris suum trigger in vitro macrophage NO production

Abstract: SUMMARY We investigated the in vitro effect of total excretory/secretory and somatic antigens from Ascaris suum adults (ESA and SA) and larvae 3 (ESL3 and SL3), and of 10 purified protein fractions from ESA components on rat alveolar macrophage nitric oxide (NO) production. Our results showed that in vitro incubation of macrophages with SA and SL3 antigens of A. suum did not result in NO release from cells, whereas incubation with ESA or ESL3 antigens resulted in the stimulation of NO production by these cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…Enolase has been found on the surface of many other pathogenic species, i.e. bacteria, fungi, and protozoa (32) with immune modulating properties (33), and has been predicted on the surface of the nematode worm Onchocerca volvulus (34) and found in in vitro culture studies in other nematodes, Ascaris suum (35) and Haemonchus contortus (36).…”
Section: Discussionmentioning
confidence: 99%
“…Enolase has been found on the surface of many other pathogenic species, i.e. bacteria, fungi, and protozoa (32) with immune modulating properties (33), and has been predicted on the surface of the nematode worm Onchocerca volvulus (34) and found in in vitro culture studies in other nematodes, Ascaris suum (35) and Haemonchus contortus (36).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have studied the effect of different antigens, somatic and excretory/secretory of larval and adult worms of nematodes, on NO production from rat alveolar macrophages. We have observed that somatic antigens from the third stage larvae and excretory/secretory antigens from adult worms in Toxocara canis and Strongyloides venezuelensis stimulated the NO production from alveolar macrophages ([30]; unpublished data ); similar data were found with Ascaris suum antigens [31]. …”
Section: Do Helminths Induce No Production By the Host Cells And mentioning
confidence: 64%
“…We also analyzed different parasite proteins to define the specific Dirofilaria immitis somatic adult-worm antigens involved in host cell NO secretion. We identified a parasitic specific component (DiID35.3) which does not belong to the endosymbiont Wolbachia and which is intimately related to proteins of the Immunoglobulin Superfamily (ISP) group, triggering NO release from macrophages in a dose-dependent and specific manner [31]. …”
Section: Do Helminths Induce No Production By the Host Cells And mentioning
confidence: 99%
“…Significant alteration in IL-8 signalling was observed after mice were immunised with our vaccine candidate, involving up-regulation of receptors for IL-8, MMP9 and CXCR2. Nitric oxide production has been studied in vitro in infection caused by helminths involving Trichinella spp, Dirofilaria immitis and Ascaris suum antigens; a correlation has been found between antigen-dependent stimulation and nitric oxide levels [6365]. Nitric oxide could regulate inflammation produced by egg release, prevent hepatic cell damage, the spread of damage in the liver and reduce granuloma formation by S. mansoni [66].…”
Section: Discussionmentioning
confidence: 99%